Economic convergence and regional development strategies in Spain: The case of Galicia and Navarre - Andrés Rodríguez-Pose (EIB Papers, 2000)
In this paper, I will try to analyse the factors behind the lack of relative convergence in Spain since the early 1980s by focusing on two regions which have had different economic trajectories in the last two decades: Navarre, a region which, despite being located in the declining northern Spanish fringe, has managed to grow at a slightly higher pace than the rest of Spain; and Galicia, one of the regions which has undergone a relative decline since the beginning of the 1980s. The paper is structured in four further Sections. The next section deals with the economic performance of Spanish regions since 1980, focusing specially on the problem of lack of regional convergence in recent years. Section 3 includes the reasons behind the selection of the two case studies, despite the fact that neither Navarre is the most dynamic, nor Galicia is the least dynamic region in Spain, as well as a description of the changing structure of the economies of the two regions. The fourth Section deals with the existing institutional framework for designing and implementing regional development policies in these regions, and with the assistance programmes actually implemented at the regional, national and EU levels. This is followed in Section 5 by a discussion of the factors behind the success and failure of regional development policies. Finally, the paper concludes with a brief discussion of how the experiences of these two regions can be generalised to other regions.
Keywords: 330; Entwicklungskonvergenz; Spanien; Galicien (Spanien); Navarra